2020
DOI: 10.1097/j.pain.0000000000001958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of using text message interventions for the management of musculoskeletal pain: a systematic review

Abstract: Musculoskeletal pain is the greatest cause of disability worldwide. Owing to its increasing prevalence and burden, the importance of affordable treatments has been highlighted. Text message interventions are accessible, low cost, and effective in promoting healthy behaviour and managing chronic diseases. However, little is known about their role in musculoskeletal pain. This systematic review was conducted to appraise the literature on the effects of text messages (as an intervention or a component of an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…49 Further, the quality of the evidence of relevant experimental studies has already recently been critically appraised. 33 Our study is limited to peer-reviewed studies published in the English language and indexed in four online databases. We anticipate that information of most relevance to our questions will be contained in the peer-reviewed literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Further, the quality of the evidence of relevant experimental studies has already recently been critically appraised. 33 Our study is limited to peer-reviewed studies published in the English language and indexed in four online databases. We anticipate that information of most relevance to our questions will be contained in the peer-reviewed literature.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from experimental studies of the effectiveness of text messaging interventions for managing MSK pain conditions has recently been comprehensively synthesised. 33 We will build on this work by describing studies relating to the design of messaging systems for MSK conditions, and by synthesising the results from both experimental and observational studies. Because we aim to map the literature, as is common practice with scoping reviews, we will not assess the methodological quality or risk of bias of included studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in response to texting pain, the user might receive a message offering pain coping strategies (eg, "breathe in slowly to a count of four, breathe out for six") or informational reassurance (eg, "pain may flare up for many reasons-not necessarily due to tapering"). This functionality is common and feasible in mHealth technology [28,30].…”
Section: Implications For Design and Functionalitymentioning
confidence: 99%
“…mHealth interventions have been found to be effective in supporting people to manage a variety of complex chronic health conditions, including diabetes, cardiovascular disease, and obesity [21][22][23][24][25]. mHealth has also been used effectively to support the cessation of addictive substances [26][27][28], to improve people's ability to cope with chronic pain, and to enhance perceived quality of life [29][30][31][32]. One study found that a narrative (patient testimony) educational video about opioid tapering increased patients' tapering self-efficacy to a greater degree than a pamphlet with the same information [33].…”
Section: Introductionmentioning
confidence: 99%